Discrete element method parameter calibration and validation of wheat based on the Tavares model - Huapo Jia; Bo Feng; Wenbin Wu; Kexuan Yang (PLoS ONE, 2026)
Existing discrete element studies on wheat predominantly utilize simplified models, which fail to accurately characterize differences in fracture behavior resulting from the anisotropic structure of wheat grains. Furthermore, there is a lack of systematic calibration for the core parameters of the crushing model employed in these studies. To address these issues, this study systematically calibrated and validated the contact parameters and crushing parameters of wheat grains using the Tavares crushing model. Employing a combined approach of physical experiments and simulation, contact parameters between wheat grains and the grinding roller surface material (white cast iron), as well as between wheat grains, were first determined. The accuracy of these parameters was validated via angle of repose tests. Subsequently, uniaxial compression tests and drop hammer impact tests were conducted to systematically calibrate the fracture energy distribution characteristics and cumulative damage coefficient for the Tavares model. Results indicate that: the elastic restitution coefficient, static friction coefficient, and rolling friction coefficient between wheat grains and white cast iron are 0.399, 0.426, and 0.179, respectively; the corresponding coefficients for wheat grain-wheat grain contact are 0.405, 0.322, and 0.039. The deviation between the simulated and experimental values of the angle of repose obtained using these parameters is only 1.05%. The fracture energy of wheat grains follows a log-normal distribution, with a median value of 2069.78 J/kg and a cumulative damage coefficient of 5. Substituting the calibrated parameters into the Tavares model enabled the establishment of a wheat compression-fracture simulation model that accounts for grain anisotropy. Quantitative comparison between the simulated and experimental compression force-displacement curves shows that the relative errors of the ensemble-averaged fracture force and fracture energy are 4.47% and 1.27%, respectively, providing objective quantitative validation for the calibrated model parameters. This study provides a theoretical foundation and practical tool for numerical simulation and process optimization in wheat roller milling, and offers significant reference value for improving wheat processing quality and efficiency.